Hubungan Gaya Hidup dengan Kejadian Hipertensi pada Lansia di Puskesmas Kartasura - Atrina Madina Suci; Kartinah Kartinah (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to empirically analyze the relationship between lifestyle and the incidence of hypertension among older adults, while offering updated evidence on how behavioral factors contribute to predicting hypertension risk in the elderly population. The research addresses a gap in previous studies by integrating four lifestyle components physical activity, dietary habits, sleep patterns, and smoking behavior into a single correlational model within a primary healthcare setting. A quantitative descriptive correlational design with a cross-sectional method was applied to 85 older adults at the Kartasura Public Health Center. The findings indicate that most respondents exhibited unhealthy lifestyle patterns, and 84.7% were identified as having hypertension. Spearman Rho analysis produced a significance value of p = 0.000 and a correlation coefficient of r = 0.523, demonstrating a significant moderate relationship between lifestyle and hypertension. These results reinforce the evidence that daily behavioral practices play a substantial role in elevating blood pressure among older adults. Practically, this study highlights the urgency of implementing behavior-based health promotion interventions, including increased light physical activity, education on low-sodium diets, sleep management, and smoking cessation programs. It is recommended that primary healthcare centers develop structured and sustainable lifestyle-modification programs tailored for older adults to effectively reduce hypertension risk.